Effects of caffeine on anorectal manometric findings - Supatra Lohsiriwat (2018)
PURPOSE: This study was designed to evaluate the effects of caffeine on anorectal function by anorectal manometry. METHODS: Ten healthy subjects were studied. They drank 200 ml of water and later 200 ml of a solution that contained caffeine 3.5 mg/kg body weight. The anorectal manometric study was divided into three periods: basal, water, and caffeine; each period lasted 45 minutes. RESULTS: After the ingestion of water, the basal anal sphincter pressure showed no change during the 45-minute recording, whereas after caffeine consumption the basal anal sphincter pressure increased at 10 minutes (P=0.047) and 15 minutes (P=0.037). The average basal anal sphincter pressure throughout the 45 minutes was significantly higher after caffeine ingestion than after water (P=0.013). After caffeine intake, the maximum squeeze pressure increased significantly (P=0.017) compared with the basal period. Both water and caffeine consumption caused a decrease in the rectal sensory threshold for the desire to defecate. CONCLUSIONS: Caffeine 3.5 mg/kg body weight in 200 ml of water resulted in stronger anal sphincter contractions both at basal period and during voluntary squeeze. The sensory threshold was also decreased, leading to an earlier desire to defecate. Caffeine consumption may result in an earlier desire to defecate, leading to defecation if the anal sphincter can relax voluntarily. © 2008 The American Society of Colon and Rectal Surgeons.